2010
DOI: 10.1258/ijsa.2010.010252
|View full text |Cite
|
Sign up to set email alerts
|

Use of modern and traditional products to self-treat symptoms of sexually transmitted infections in South African women

Abstract: The objective of the study is to investigate products used by women self-treating symptoms of reproductive tract infections (RTIs), including sexually transmitted infections (STIs), and their methods of administration. A household survey using a multi-stage cluster sample design was undertaken in KwaZulu-Natal, South Africa. Women aged 18-60 years were interviewed (n = 867) and information was collected on demographics, reproductive health and sexual behaviours. A fifth of women reported having RTI/STI symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ingestion, insertion, application, and steaming were also used as a treatment of ill-health symptoms and pregnancy-related issues, as reported in a South African study (Beksinska et al, 2010). Other methods of treatment mentioned referred to a scarification process in the genital area and tattoos of the vulva or labia.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion, insertion, application, and steaming were also used as a treatment of ill-health symptoms and pregnancy-related issues, as reported in a South African study (Beksinska et al, 2010). Other methods of treatment mentioned referred to a scarification process in the genital area and tattoos of the vulva or labia.…”
Section: Discussionmentioning
confidence: 99%
“…There has been extensive research into women’s intravaginal cleansing practices in sub-Saharan Africa. In South Africa, studies in the general population have found that the percentage of women reporting intravaginal cleansing varies considerably, from 13 % in the Western Cape to 87 % in Gauteng [514], although the prevalence was higher among commercial sex workers [15–18]. Intravaginal cleansing is practiced for a variety of reasons such as maintaining vaginal hygiene and health, treating infections, and preparing for sex [5].…”
Section: Introductionmentioning
confidence: 99%